2002
DOI: 10.17221/3511-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for determination of deoxynivalenol in cereals and flours

Abstract: An effective and fast method for determination of deoxynivalenol (DON) in cereals and flours has been developed. The immunoaffinity column was used for the isolation of DON from wheat, corn, rice and flour extract. The determination was carried out by using the HPLC/UV method. The limit of detection was 0.02 mg/kg. The recoveries for the assay range 0.1 to 2 mg/kg were generally higher than 80%, ranging from 83 to 96% with an average relative standard deviation of 3.8%. The trueness of the method using the DON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…HPLC-UV is preferable instrument for quantification. Shepherd et al monitored DON standard solutions stability at 220 nm [35]; Visconti et al detected NIV, DON, fusarenone X (FusX) and 3-AcDON at 225 nm [36]; Kotal and Ok-at 218 nm [37,38]; Yang-at 224 nm [39]. Within the European Commission project aimed at producing and certifying calibrants for the determination of B-trichothecenes, Krska et al applied a wide spectrum of analytical techniques for the estimation of purity and contaminants levels in standard solutions of DON, 3-AcDON, 15-AcDON and NIV [40].…”
Section: Type B Trichothecenesmentioning
confidence: 99%
“…HPLC-UV is preferable instrument for quantification. Shepherd et al monitored DON standard solutions stability at 220 nm [35]; Visconti et al detected NIV, DON, fusarenone X (FusX) and 3-AcDON at 225 nm [36]; Kotal and Ok-at 218 nm [37,38]; Yang-at 224 nm [39]. Within the European Commission project aimed at producing and certifying calibrants for the determination of B-trichothecenes, Krska et al applied a wide spectrum of analytical techniques for the estimation of purity and contaminants levels in standard solutions of DON, 3-AcDON, 15-AcDON and NIV [40].…”
Section: Type B Trichothecenesmentioning
confidence: 99%
“…A previous study showed that for isolation and increases maximum absorbance in UV range DON was passes through immunoaffinity column,[13] whereas in the present study DON was separated using alumina-silica-activated charcoal (1:1:1), which is more economic and easier.…”
Section: Discussionmentioning
confidence: 85%
“…All grain samples were ground in an Ultra Centrifugal Mill ZM 200 (Retsch, Germany) with 0.8 mm sieve. The ground spring wheat samples were analysed according to the method previously validated for the determination of DON in cereals with some modifications (Kotal, Radova, 2002). For extraction, 10 g of ground sample was placed into 100 ml glass bottle and then 40 ml deionized water and 2 g PEG were added.…”
Section: Methodsmentioning
confidence: 99%